2019
DOI: 10.1021/acs.cgd.8b01230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-nanoparticle Architecture on Cycling Performance of MnO2 Battery Cathodes through Thermal Tuning of Polymorph Composition

Abstract: Reversible cycling of MnO2 cathodes remains a challenge in alkaline rechargeable battery development. In prior work, we have developed new platelet shaped MnO2 nanoparticles with stable performance in LiOH electrolyte for over 50 cycles. In this study, the effects of sub-nanoparticle organization of MnO2 polymorphs on cycling performance, phase activation, and charge/​discharge mechanisms in LiOH electrolyte are investigated by ex situ X-ray powder diffraction (XRD). Different phase compositions with the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[ 92,93 ] The general failure mechanism of MnO 2 cathode in the alkaline electrolyte is ascribed to the partial irreversible conversion reactions between MnO 2 and the reduced Mn 2 O 3 and Mn(OH) 2 , or the gradual dissolution of MnO 2 into the strong alkaline electrolytes (Figure 2). [ 94–98 ] In order to improve the MnO 2 cathode instability issue, researchers have developed various strategies such as utilizing mixed KOH and LiOH instead of pure KOH as the electrolyte, [ 99–101 ] or different metals doping of MnO 2 . [ 102–105 ] It was found that the battery capacity retention rate and the number of cycles can be largely increased.…”
Section: The Development Of Mn‐based Batteries With Different Mechanismsmentioning
confidence: 99%
“…[ 92,93 ] The general failure mechanism of MnO 2 cathode in the alkaline electrolyte is ascribed to the partial irreversible conversion reactions between MnO 2 and the reduced Mn 2 O 3 and Mn(OH) 2 , or the gradual dissolution of MnO 2 into the strong alkaline electrolytes (Figure 2). [ 94–98 ] In order to improve the MnO 2 cathode instability issue, researchers have developed various strategies such as utilizing mixed KOH and LiOH instead of pure KOH as the electrolyte, [ 99–101 ] or different metals doping of MnO 2 . [ 102–105 ] It was found that the battery capacity retention rate and the number of cycles can be largely increased.…”
Section: The Development Of Mn‐based Batteries With Different Mechanismsmentioning
confidence: 99%
“…The calcination treatment could lead to the collapse of the 1 × 2 channels to smaller 1 × 1 channels, thus leading the transformation of γ-MnO 2 to β-MnO 2 . [32] Compared to the hydrothermal condition, the phase transformation induced by post-calcination forms more abundant oxygen defects, benefitting from the intrinsic incomplete lattice rearrangement. We find that the oxygen defects favor the reactants adsorption and *NH 2 formation.…”
Section: Introductionmentioning
confidence: 99%